Вioengineering technologies in the treatment of nervous system pathology - Liubich, L.D.; Staino, L.P.; Yehorova , D.M.; Oleksenko, N.P.; Medvediev, V.V. (Problems of Environmental Biotechnology, 2023)
Cell therapy using stem/progenitor cells (SPCs), regenerative biomaterials, tissue engineering technologies, and their combination is considered an effective strategy for the treatment of central nervous system (CNS) pathology. Bioengineering technologies are of particular importance in cases of CNS traumatic lesions, primarily for the purpose of filling traumatic cavities and providing adsorption loci for transplanted or endogenous cells; as well as to suppress the apoptosis, inflammation, glial scars formation and stimulation of neurogenesis, axons sprouting and angiogenesis. The aim – to study the effect of implantation of fibrin matrix (FM) associated with neural SPCs on the rat spinal cord tissue after spinal cord injury.